Queratocono y miopía astigmática irregular en paciente femenino de 22 años. - Villacis Moran, Italo Fernando (2018)
Keratoconus is characterized by thinning, weakening and protrusion of the cornea, of unknown etiology, which causes decreased vision. Although it is degenerative; It is also chronic, which should be taken advantage of by the professional, and with the help of the patient attending an annual or semi-annual check, we could detect in time and be able to apply, a respective treatment according to the stage that the pathology presents. Since if it is not treated in time unfortunately the patient will lose a percentage of his vision. For this reason our goal as an optometrist is to provide primary health to give a higher quality and efficiency in the life of our patient. Female patient of 22 years, attends the consultation referring distant vision loss with correction in use. He had a periodical evaluation in six months, but returned to three years and from that time he combines the use of soft contact lenses with those of saddle. We realize that the patient gave little interest and did not attend the optometric controls, which at the beginning only presented astigmatic myopia but returned because her vision was distorted and when performing Retinoscopy she found scissor reflexes that gives a suspicion of a keratoconus.